(untitled) (Journal of Economic Research & Business Administration, 2016)
In modern conditions of development the energy observation plays the key role because it is the complex technical-economical inspection of organization which is being made to receive authentic information on volume of energy resources used to identify the structure and effectiveness of energy expenses of organization, to detect the possibilities of energysaving and increase of energy effectiveness. By the results of energy observation the report and energy passport of fuel-energy consumer are being generated. The aim of energy audit is to evaluate the effectiveness of fuel-energy usage and work out effective measures to decrease company’s expenses. In article the steps of energy audit that stimulate its effective conducting are improved.